Nzikitanza – A piece on the resistance against the MUOS in Niscemi, Sicily - Messina, Marcello (Revista Vórtex, 2015)
Nzikitanza for accordion, violin, cello and tape was written in 2012 as a reflection on the deployment of Sicilian territory for NATO and US military operations. In particular, the piece was inspired by the then newly formed resistance committee against the MUOS in Niscemi. This brief commentary will illustrate a priori and a posteriori reflections on the status of the piece as a contribution to forms of antagonistic culture.